DESAIN LEAD RUBBER BEARING PADA PERENCANAAN GEDUNG RUMAH SAKIT “X” DI KOTA PADANG DENGAN LAYOUT MEMANJANG - Shandy, Fara Dilla; Yusmar, Fajri (Jurnal Applied Science in Civil Engineering, 2024)
A hospital is a vital building with high sensitivity to external disturbances due to its structural vulnerability to damage caused by external factors such as natural disasters, especially earthquakes. Padang, a city located near the Sumatra Fault Zone, is an area with a high seismic risk. Additionally, the building under study is affected by irregularity due to land constraints, resulting in an elongated layout that is susceptible to torque. Furthermore, buildings with a rectangular configuration have different stiffness and inertia along each axis, which can lead to varying structural responses to lateral loads such as wind and earthquakes. The geometry of the structure also influences the magnitude of stiffness and inertia, causing variations in the earthquake loads experienced. This research aims to design a Lead Rubber Bearing (LRB) isolator for the planning of the "x" hospital building in Padang with an elongated layout. The goal is to determine the type or characteristics of LRB components that meet the structural requirements. Based on the analysis, the LRB design includes an isolator diameter of 600 mm, a lead plug diameter of 80 mm, and an isolator height of 400 mm, which provides an effective vertical stiffness of 1670 kN/mm, effective stiffness in the x and y directions of 0.66 kN/mm, and effective damping of 11.14% in the x direction and 11.15% in the y direction